2‐undecanone protects against fine particles‐induced heart inflammation via modulating Nrf2/HO‐1 and NF‐κB pathways. Issue 7 (14th March 2022) - Jiao, Yuhang; Wang, Shaopeng; Jiang, Liping; Sun, Xiance; Li, Jing; Liu, Xiaofang; Yao, Xiaofeng; Zhang, Cong; Wang, Ningning; Deng, Haoyuan; Yang, Guang
Abstract: Exposure to air pollution has been closely associated with some cardiovascular disease. One of the mechanisms of PM2.5 ‐mediated heart injury may be to promote inflammation. We aim to investigate whether the main extract of Houttuynia cordata, 2‐undecanone, can prevent the inflammation caused by PM2.5, and to reveal the underlying mechanisms. The results showed that PM2.5 increased the expression of certain inflammatory cytokines, and caused oxidative damage in BALB/c mice and H9C2 cells. Supplementation with 2‐undecanone attenuated this PM2.5 ‐induced inflammatory injury and oxidative damage. Further, we elucidated that the protective effect of 2‐undecanone may be associated with NF‐κB and Nrf2/HO‐1 pathways. The NF‐κB pathway was distinctly activated after treated by PM2.5, which can be blocked by 2‐undecanone, accompanied by increasing Nrf2 and HO‐1 levels. To figure out the relationship between NF‐κB and Nrf2/HO‐1 pathways, we knocked down Nrf2 gene. NF‐κB pathway proteins and downstream inflammatory cytokines were significantly increased after treatment with PM2.5, while 2‐undecanone could decrease expression of these proteins. In conclusion, it is possible that 2‐undecanone can induce the expression of the antioxidant enzyme HO‐1 by activating Nrf2, thereby reducing NF‐κB pathway and inflammatory damage of mouse myocardium caused by PM2.5 exposure.